Do foreign direct investment, trade and their interactions affect economic growth in Indonesia? - Heppi Millia; Ernawati Ernawati; Heriberta Heriberta (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2023)
This study examines the direct and indirect impacts of foreign direct investment, exports, and imports on Indonesia's long-term and short-term economic growth. To this end, we used quarterly data for 2005.1–2021.4 sourced from Statistics Indonesia, the Bank of Indonesia, and the Bank of St. Louis. The analytical tools employed were the autoregressive model of the lag distribution (ARDL) and the error correction model (ECM-ARDL). Findings showed that foreign direct investment, exports, and imports directly affected Indonesia's economic growth. However, while the two formers had an impact only in the short run, the latter also did so in the long run. In addition, foreign direct investment also indirectly influenced economic growth through exports in the short and long run, whereas this was not the case with imports. Based on these findings, we argue for policy recommendations. To begin with, the government should encourage foreign direct investment, which may gradually replace imported raw materials with local raw resources, thereby creating an upstream connection while slowing the rate of imports. Furthermore, the government needs to adopt a policy of downstream processing of primary commodities into industrial commodities to increase export value and expand employment opportunities.